Pola-pola Persepsi Belanda terhadap Islam di Indonesia - Ali-Fauzi, Ihsan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
This is the first work in book form which attempt to portray Westren perception, particularly the Dutch, of Islam in Indonesia during a long period of 1596 to 1942. According to Steenbrink, author of this work, in the long history of Dutch colonialism in the archipelago, there can be identified four major patterns of Dutch perception of an attitude toward Islam in Indonesia. All these patterns which, by and large, viewed Islam in a negative way constantly persited, even though with some small cases of exception.DOI: 10.15408/sdi.v3i3.804